Monkeypox and human metapneumovirus in India: addressing preparedness and challenges amid emerging threats - Verma, Aditi; Ara , Anjum (International Journal Of Community Medicine And Public Health, 2025)
The advent of monkeypox (Mpox) and the human metapneumovirus (hMPV), along with serious public health consequences, emphasizes the global vulnerability to these diseases that were earlier endemic in other countries. India's high population density poses unique disease management and prevention challenges against such infections. However, India still has the advantage of having a huge healthcare workforce. Medical practitioners in primary health care services are ideally positioned to screen and intervene early to contain such diseases and reduce these viral outbreaks. Since the typical Mpox rash is extensive and involves the oral cavity and perioral structures frequently, accompanied by cervical lymphadenopathy, dentists could also play a major role by routinely embedding an efficient screening of Mpox cases into dental health services and providing timely referrals to appropriate authorities and help in the containment of the disease. While the respiratory system is the primary target of the hMPV, the secondary effects or the systemic nature of these viral infections may result in some indirect consequences in the oral cavity. The recent increasing spread of Mpox and hMPV into non-endemic countries has raised questions regarding global readiness and response measures to combat these infections in India. Hence, this paper examines India's current strategies including the healthcare infrastructure, surveillance systems, public health policies, the role of medical and oral healthcare workers, challenges, and recommendations for strengthening preparedness against Mpox and hMPV, drawing on global best practices.